Effective transfer of micron-size graphene to microfibers for photonic applications. (January 2016) - Wu, Xiaoqin; Yu, Shaoliang; Yang, Huiran; Li, Wenlei; Liu, Xueming; Tong, Limin
Abstract: We demonstrate an effective approach to transferring micron-size CVD graphene layers onto freestanding microfibers. With micro-manipulation, the coating position and length of the graphene films can be precisely controlled. By coating micrometer-scale (e.g., 20 μm) graphene films onto microfibers with diameters down to 1 μm, we can achieve significantly enhanced light–graphene interaction (e.g., a low saturable-absorption threshold of 40 MW/cm 2 ) and simultaneously maintain a high transmission (73% in maximum) as well. In addition, we use these microscale CVD graphene-coated microfibers (GCMs) as saturable absorbers for all-optical modulation at 1550-nm wavelength with a modulation depth of 12% and passively mode-locked fiber lasing with pulse duration down to 970 fs.